"A Guy 'Does' and You Don't, They Do You Instead": Young People's Narratives of Gender and Sexuality in a Low-Income Context of South Africa. (December 2018) - Graham, Lauren; Mphaphuli, Memory
The intensive research focus on young people's sexuality in relation to risk means that young people's sexuality is often pathologized. We thus miss out on the day-to-day lived realities of how young people negotiate gender identity as well as sexuality in complex, nuanced, but normal ways. This article contributes to an emerging body of research that highlights how young people negotiate gender identity and sexuality in their day-to-day lives, by focusing on the narratives of young persons engaged in heteronormative relationships in a resource constrained setting in South Africa. We offer insights into dominant, but also alternative discourses of gender and sexuality that are not highlighted in the literature in this field. Furthermore, we offer new empirical insights into how socioeconomic status shapes their gender identity, beliefs about sex and their sexual practices, contributing to a small but emerging field of research engaging with the intersection of gender, sex, and socioeconomic status.